EVALUASI PENERAPAN PROGRAM CONDITIONAL CASH TRANSFER (CCT) - suryanto, suryanto; Dwi Aryanti, Titin (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2025)
One of the government's efforts to overcome poverty is by implementing the Conditional Transfer (CCT) program. In short, CCT is assistance provided to beneficiaries with certain conditions. The CCT currently being implemented in the City of Surakarta is the Family Hope Program (PKH) and Non-Cash Food Assistance (BPNT). This research intends to evaluate the conditional cash transfer (CCT) program which focuses on the Regional Apparatus Organization (OPD) of the Surakarta City Social Service. The research approach used is quantitative, using the Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI) methods. The research results show that there are still several attributes that require improvement to be able to reduce poverty to the maximum. The results of the overall satisfaction index for the people of Surakarta City show 62.07%, which indicates a Very Poor interpretation where service users or the people of Surakarta City feel dissatisfied with the performance of service providers or the government. The implication of this research is that the government can improve performance on high priority attributes, especially in the planning dimension. There needs to be good cooperation between the government, lower level officers and the community in maintaining performance in the implementation dimension.